The Psoriasis Risk Allele HLA-C*06:02 Shows Evidence of Association with Chronic or Recurrent Streptococcal Tonsillitis - Haapasalo K; Koskinen LLE; Suvilehto J; Jousilahti P; Wolin A; Suomela S; Trembath R; Barker J; Vuopio J; Kere J; Jokiranta TS; Saavalainen P (AMER SOC MICROBIOLOGY, 2022)
Pharyngeal tonsillitis is one of the most common upper respiratory tract infections, and group A streptococcus is the most important bacterial pathogen causing it. While most patients experience tonsillitis only rarely, a subset of patients suffers from recurrent or chronic tonsillitis or pharyngitis. The predisposing factors for recurring or chronic forms of this disease are not yet fully understood, but genetic predisposition has been suggested. A genetic association study using Illumina's Immunochip single-nucleotide polymorphism (SNP) array was performed to search for new genetic biomarkers in pharyngeal tonsillitis. More than 100,000 SNPs relevant to immune-mediated diseases were analyzed in a cohort of 95 patients subjected to tonsillectomy due to recurrent/chronic tonsillitis and 504 controls. Genetic association between the cases and controls showed strongest association with two peaks in the HLA locus (odds ratio [OR], 3.7 to 4.7; P = 4.9 x 10(-6) to 5.7 x 10(-6)). Further analysis with imputed classical HLA alleles suggested the known psoriasis risk allele HLA-C*06:02 as a risk factor for tonsillitis (P = 4.8 x 10(-4); OR, 2.3). In addition, the imputed HLA haplotype HLA-C*06:02/HLA-B*57:01, a reported risk haplotype in psoriasis, had the strongest risk for tonsillitis (P = 3.2 x 10(-4); OR, 6.5). These findings further support the previously reported link between streptococcal throat infections and psoriasis.